Dynamics of Civil Structures. Proceedings of the 37th IMAC, a Conference and Exposition on Structural Dynamics 2019 /: Proceedings of the 37th IMAC, a Conference and Exposition on Structural Dynamics 2019. Volume 2 : ([2020]) - Unknown
No abstract available